2014
DOI: 10.1007/s00894-014-2509-9
|View full text |Cite
|
Sign up to set email alerts
|

DFT study of the effect of solvent on the H-atom transfer involved in the scavenging of the free radicals ●HO2 and ●O2 − by caffeic acid phenethyl ester and some of its derivatives

Abstract: H-atom transfer from caffeic acid phenethyl ester (CAPE), MBC (3-methyl-2-butenyl caffeate), BC (benzoic caffeate), P3HC (phenethyl-3-hydroxycinnamate), and P4HC (phenethyl-4-hydroxycinnamate) to the selected free radicals (·)HO2 and (·)O2(-) was studied. Such a transfer can proceed in three different ways: concerted proton-coupled electron transfer (CPCET), electron transfer followed by proton transfer (ET-PT), and proton transfer followed by electron transfer (PT-ET). The latter pathway is sometimes competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…The B3LYP hybrid functional was used throughout the computations; the use of this functional is because of the previous work [25,26] done on the three molecular systems where the B3LYP where used. This functional consists of the Becke's three parameters exact exchange functional (B3) [43] combined with the non-local gradient corrected correlation functional (due to Lee-Yang-Parr (LYP)) [44].…”
Section: Dft Oniom and Basis Setsmentioning
confidence: 99%
See 2 more Smart Citations
“…The B3LYP hybrid functional was used throughout the computations; the use of this functional is because of the previous work [25,26] done on the three molecular systems where the B3LYP where used. This functional consists of the Becke's three parameters exact exchange functional (B3) [43] combined with the non-local gradient corrected correlation functional (due to Lee-Yang-Parr (LYP)) [44].…”
Section: Dft Oniom and Basis Setsmentioning
confidence: 99%
“…These compounds were studied experimentally on the DNA damage by Sestili et al [24] where they showed that all these three compounds are able to chelate Fe 2+ . We did in our previous work [25,26] the theoretical study of their antioxidant activity. Therefrom, we found that MBC was the good antioxidant but not more than quercetin, the one of the best antioxidant known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atom transfer can be further classified into several subtypes: hydrogen atom transfer (HAT), concerted proton-coupled electron transfer (CPCET), electron transfer followed by proton transfer (ET-PT), proton transfer followed by electron transfer (PT-ET), and sequential proton loss electron transfer (SPLET) among others [35]. As a stable free radical, DPPH‚ can be reduced by phytophenols to DPPH-H (Equation (3)) [36].…”
Section: Figure 3 the Protective Effect Of Dihydromyricetin (Dhm) Agmentioning
confidence: 99%
“…Molecules 2016, 21, 604 6 of 13 sequential proton loss electron transfer (SPLET) among others [35]. As a stable free radical, DPPH• can be reduced by phytophenols to DPPH-H (Equation (3)) [36].…”
Section: Figure 3 the Protective Effect Of Dihydromyricetin (Dhm) Agmentioning
confidence: 99%